Monkeypox: A review of a zoonotic disease of global public health concern - Yusuf Amuda Tajudeen; Habeebullah Jayeola Oladipo; Abdulbasit Opeyemi Muili; Joy Ginika Ikebuaso (Tabriz University of Medical Sciences, 2023)
Background: The rising circulation of the monkeypox virus while the COVID-19 is still ongoing in non-endemic countries is a significant global health threat. In this article, we have discussed the epidemiology, aetiology, and pathogenesis of the monkeypox virus to provide our current knowledge of the disease. Also, we discussed the ongoing efforts of the international health organizations to curtail the present epidemic and we finally provide recommendations for early detection and response. Methods: We did a rapid literature search on PubMed, EMBASE, World Health Organization (WHO), the Centers for Disease Control and Prevention (CDC), and other trusted databases for recent articles (1958-2022) published in English-focusing on the outbreaks of monkeypox disease, epidemiology, pathogenesis, aetiology, prevention, and control in endemic and non-endemic countries. Keywords such as "Monkeypox", "Monkeypox virus", "Poxviridae", "Orthopoxvirus", "Smallpox", and "Smallpox Vaccine" were considered in our search based on MESH medical subject headings. Results: Our review highlights four important findings. First, a cumulative of 1285 monkeypox cases have been documented and reported by the WHO in non-endemic countries as of June 8, 2022. Second, international travel contributes to the increase in cases in non-endemic countries. Third, the origin of the outbreak, the pattern of transmission, and the risk of infections is not fully understood. Fourth, there is an ongoing effort by the WHO, CDC, and other international health organization to control the spread of the monkeypox disease. Conclusion: Our findings underline the need to reassess research priorities on the origin, transmission pattern, and risk factors for infection of monkeypox. Also, we provide recommendations under the One Health spectrum to prevent further spread of the disease.